Economics of forest carbon storage and the additionality principle - Tahvonen, Olli; Rautiainen, Aapo (Elsevier, 2017)
The ability of forests to store carbon is vital in maintaining the preset climate conditions, but is not systematically included in forest management or land-use decisions. Economic reasoning suggests subsidizing carbon storage, but empirical models show that this may easily more than double stand-level bare land values. Subsidization may thus be expensive, as it requires paying for all storage, including what would otherwise be obtained for free. To limit the consumption of public funds, the regulator may apply an additionality principle and solely subsidize storage exceeding a baseline level. We show that the commonly applied stand-level analysis suggests that the additionality principle could be applied to optimal rotation decisions without distortions. However, applying a forest vintage model with endogenous prices and land allocation decisions shows that similar application of the additionality principle causes distortions to both land allocation and optimal forest rotation. Nevertheless, subsidizing carbon storage by forest site productivity tax may still be preferable among the second-best policies. The distortions can be avoided by eliminating excessive subsidies by general land taxation irrespective of whether the land is used for forestry or agriculture.
Keywords: optimal rotation; forest vintages; additionality; cabon sequestration; forests; afforestation